Genetically predicted serum testosterone and risk of gynecological disorders: a Mendelian randomization study - Zhao, Benzheng; Wang, Zhenpeng; Liu, Dongzhen; Zhang, Songling (Frontiers in Endocrinology, 2023)
Background: Testosterone plays a key role in women, but the associations of serum testosterone level with gynecological disorders risk are inconclusive in observational studies.We leveraged public genome-wide association studies to analyze the effects of four testosterone related exposure factors on nine gynecological diseases. Causal estimates were calculated by inverse variance-weighted (IVW), MR-Egger and weighted median methods. The heterogeneity test was performed on the obtained data through Cochrane's Q value, and the horizontal pleiotropy test was performed on the data through MR-Egger intercept and MR-PRESSO methods. "mRnd" online analysis tool was used to evaluate the statistical power of MR estimates.The results showed that total testosterone and bioavailable testosterone were protective factors for ovarian cancer (odds ratio